Cocoon 2 [videorecording (DVD)] : the return - Ameche, Don; Brimley, Wilford, 1934-2020-; Cronyn, Hume; Tandy, Jessica; Guttenberg, Steve, 1958-; McPherson, Stephen
In this sequel to the hit film, Cocoon, the adventurous old-timers who left Earth for the alien utopia Antarea, return on a rescue mission. Although accustomed to their new peaceful, problem-free planet, they realize the joys they left behind after they are reunited with their stunned families. Yet for all their happiness, they must once again confront the human frailties of their past.